2016
DOI: 10.22436/jnsa.009.07.02
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation analysis in a discrete SIR epidemic model with the saturated contact rate and vertical transmission

Abstract: The aim of paper is dealing with the dynamical behaviors of a discrete SIR epidemic model with the saturated contact rate and vertical transmission. More precisely, we investigate the local stability of equilibriums, the existence, stability and direction of flip bifurcation and Neimark-Sacker bifurcation of the model by using the center manifold theory and normal form method. Finally, the numerical simulations are provided for justifying the validity of the theoretical analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In recent years, due to infectious diseases data collected based on periods of days, weeks, months, and years, we have seen more attention being given to a great deal of practical real life problems in epidemiology depicted by discrete-time epidemic models described using difference equations. Although, in recent times, an increasing attention has been given to the discrete epidemic models (see [2,8] and the references cited therein), the research in the context of the nonlinear dynamic characteristics of the discrete systems is relatively few, compared with the amount of studies performed in the literature about the continuous systems. With their unique dynamic characteristics, the discrete systems are able to depict many practical problems in the real life, in particular in the context of epidemiology (see [9][10][11][12] and the references cited therein)…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, due to infectious diseases data collected based on periods of days, weeks, months, and years, we have seen more attention being given to a great deal of practical real life problems in epidemiology depicted by discrete-time epidemic models described using difference equations. Although, in recent times, an increasing attention has been given to the discrete epidemic models (see [2,8] and the references cited therein), the research in the context of the nonlinear dynamic characteristics of the discrete systems is relatively few, compared with the amount of studies performed in the literature about the continuous systems. With their unique dynamic characteristics, the discrete systems are able to depict many practical problems in the real life, in particular in the context of epidemiology (see [9][10][11][12] and the references cited therein)…”
Section: Introductionmentioning
confidence: 99%
“…The discrete-time model is capable of producing extremely complicated dynamics, even in a one-dimensional instance [14]. Many interesting and important research works can be found in [15][16][17][18][19] and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…where m is the Allee threshold and all parameters are positive. Currently, some studies about the biological system are using the discrete time model (see for example [11][12][13][14][15]). The main reason is related to the statistical data of the population which is collected in discrete time.…”
Section: Introductionmentioning
confidence: 99%